ODWIECZNE ZDERZENIE WYOBRAŻEŃ O TYM, JAK FUNKCJONUJE ŚWIAT: KONTRAST WIZJI I PROPONOWANYCH INSTYTUCJI - Winiecki, Jan (Wydział Prawa i Administracji UAM, 2010)
Badania nad instytucjami ekonomicznymi, które silnie wpływają na funkcjonowanie i efekty procesów alokacji i tworzenia zasobów mają, już swoje ugruntowane miejsce w teorii ekonomii. Niewiele jednak poświęcono uwagi czynnikom kształtującym wybór takich, a nie innych instytucji w procesie historycznym. A tymczasem ci, którzy takich wyborów dokonują, kształtują swoje preferencje według jakichś kryteriów. Niniejszy artykuł próbuje uogólnić typy rozumowania i wynikające stąd preferencje dla koncepcji tego, jak funkcjonuje świat (i jak według tych typów rozumowania powinien funkcjonować). Autor wyodrębnia dwa typy rozumowania, które określa alternatywnie jako idealistyczno-moralistyczny oraz realistyczno-pragmatyczny, i formułuje tezę, że rodzaj proponowanych instytucji wynika z takich lub innych wyobrażeń o funkcjonowaniu świata. Najobszerniejszą część artykułu stanowi swoisty tour d’horizon przez mniej więcej 2500 lat historii z perspektywy ścierania się tych dwóch typów rozumowania. W różnych epokach preferowane instytucje państwa, społeczeństwa i gospodarki były bardzo podobne i zależały właśnie od wykazywanych preferencji dla danego typu rozumowania: od starcia idei Platona i Arystotelesa do starcia totalitaryzmów i liberalizmu w XX w. Autor kończy pesymistycznymi wnioskami. Biorąc pod uwagę trwałość ludzkich wyobrażeń o tym, jak funkcjonuje świat, nie można wykluczyć, że dysfunkcjonalne i ograniczające wolność instytucje nie będą – okresowo – wypierać instytucje sprzyjające wolności, realizacji idei państwa prawa i zdolności do tworzenia bogactwa.

Studies of economic institutions have already been well entrenched in economics in recent decades. And for good reasons. The existing, or proposed (and later imposed) institutions may dramatically affect the performance of the economies. The same quantities of production factors and other resources my result in sharply differing outputs, depending on the kind of institutional environment of a given economy. However numerous are the studies of institutional arrangements and their differing impact on economic outcomes, very little attention has been attached to the fundamental ideas of how the world works (and how it should work), which determine the preferences of one or another kind of institutions. The aim of this paper is to point to, basically, two types of reasoning in this respect. They are described, alternatively, as idealistic-moralistic and realistic-pragmatic. Each type signals a preference for a different defining criterion (collectiveness or individuality, respectively). The most extensive part of the paper is devoted to the presentation of the contest of these types of reasoning and resultant preferences for (sharply differing) types of economic institutions. This contest, as it has been shown, has continued for about two and a half thousand years: from Plato and Aristotle in ancient Greece to the totalitarian and liberal institutions of the 20th century. The paper ends with what the author sees as a pessimistic outcome. Given the long history of the contest of two types of reasoning underpinning the institutional preferences, it is highly probable that dysfunctional institutions, which result from the idealistic-moralistic type of thinking, will reassert themselves in the future as well. Inevitably, they will bring about the abridgement of freedom, disregard for the Rechtstaat, and reduction of the wealth-creation capabilities of our economies.
THE ETERNAL CONTEST OF THE CONCEPTS OF HOW THE WORLD WORKS: LINKAGES BETWEEN VISIONS AND PROPOSED INSTITUTIONS
Keywords: Instytucje ekonomiczne; Economic institutions; Historia; History; Rozumowanie idealistyczno-moralistyczne; Idealistic-moralistic reasoning; Rozumowanie realistyczno-pragmatyczne; Realistic-pragmatic reasoning